PENGARUH TNI-AU DALAM PROSES PERUMUSAN KEBIJAKAN PERTAHANAN INDONESIA TERKAIT PENGAMBILALIHAN FLIGHT INTERNATIONAL REGION (FIR) DARI SINGAPURA BERDASARKAN BIROKRATIK MODEL PERIODE 2015-2017 - Yeni Eva Eristiani, - (2018)
This study discusses Indonesia's efforts in taking over FIR from Singapore. Focus on Indonesia's efforts through the Indonesian Air Force, in carrying out its role as one of the parties involved in the Indonesian defense policy formulation process. This research has a focus on how International Flight Takeover Process (FIR) From Singapore Based on Bureaucratic Model Period 2015-2017. This study uses the concept of the Bureaucratic Model, Defense Policy and International Cooperation. The Air Force has an important role in the Indonesian policy formulation process. The Air Force in all its preparations has carried out Defense Diplomacy efforts, both Trust Building and Capacity Building. The increase in capability both externally and internally has been pursued by the Indonesian Air Force for Indonesia's readiness to take over FIR